Researching into Teaching Methods In Colleges and Universities, 1st edition (Routledge, 2020)
This is one of a series of short, practical guides aimed at lecturers and tutors in colleges and universities, to help them get started on research. It covers all aspects of teaching methods, strategies for interactive teaching methods, small and large group teaching and student learning.